2010
DOI: 10.1523/jneurosci.5049-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Microelectrode Recordings of High-Frequency Gamma Oscillations in Human Cortex during Sleep

Abstract: Gamma oscillations (40 -120 Hz), usually associated with waking functions, can be recorded in the deepest stages of sleep in animals. The full details of their large-scale coordination across multiple cortical networks are still unknown. Furthermore, it is not known whether oscillations with similar characteristics are also present in the human brain. In this study, we examined the existence of gamma oscillations during polysomnographically defined sleep-wake states using large-scale microelectrode recordings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
132
3
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(163 citation statements)
references
References 69 publications
24
132
3
1
Order By: Relevance
“…Although there is more δ-band power during SWS than wake (by definition), power in δ frequencies is present during wakefulness. Moreover, as has been previously reported, γ oscillations are present during wake and SWS (25).…”
Section: Significancesupporting
confidence: 82%
“…Although there is more δ-band power during SWS than wake (by definition), power in δ frequencies is present during wakefulness. Moreover, as has been previously reported, γ oscillations are present during wake and SWS (25).…”
Section: Significancesupporting
confidence: 82%
“…They can be evoked by various stimuli, as HFOs emerging from the somatosensory areas overlying the cortical response of the somatosensory evoked potential (Hashimoto, 2000;Ozaki and Hashimoto, 2011) or HFOs recorded from the nonepileptic occipital cortex and driven by visual tasks . A high frequency (80-120 Hz) gamma oscillation partially overlapping the frequency band of the continuous HFA has been previously reported in patients studied with large-scale microelectrode recordings in all investigated cortical areas during slow-wave sleep, in the form of short bursts, and speculated to briefly restore "microwake" activity important for memory traces consolidation (Le Van Quyen et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that coherent γ-oscillations are present during REM in magnetoencephalography (MEG) recordings (10). Evidence from extracranial EEG and iEEG recordings in epileptics shows that the synchrony of macroscopic γ is lower in SWS and REM relative to the awake state (27) and that γ-presence shows a phasic expression during SWS (11,28).…”
Section: Discussionmentioning
confidence: 99%
“…10). A recent study using microwires and intracranial electroencephalography (iEEG) recordings in the neocortex of epileptics has verified the strong presence of γ-oscillations during slow-wave sleep (SWS) (11). That study also showed a marked increase of spiking during γ, a suggestive indicator of association with cortical UP states.…”
mentioning
confidence: 89%